A tradicional Escola Normal Cearense chega ao Bairro de Fátima: formação das primeiras professoras primárias (1958 - 1960) - Araújo, Helena de Lima Marinho Rodrigues (2014)
The Normal Schools were the first institutions in Brazil to work with the education of primary teachers, particularly the female ones, contributing to improve the education in the initial courses. In Ceará, its relevant role is so notorious that it became a tradition to the society since its foundation in 1884. The main objective of this PhD research is to understand how the education of the first female primary teachers happened from 1958 to 1960 in Fatima neighborhood. The specific objectives are: keep track of the arrival of the Normal School in that neighborhood, knowing the perspectives of the “normalistas” about this change, including the building and the school´s around; to know the educational curriculum of the course, trying to understand its pedagogical aspects in relation to the institution´s the purpose: primary teachers education; to understand the class planning as well as the teaching practice preparation and to figure out what studying in the Normal School means to them, trying to understand the place that institution occupied in the normalistas’ memories. In the theoretical approach, the following concepts were used: (i) tradition, from the authors Hobsbawm (1997) and Balandier (1997); (ii) teacher education, highlighting the authors Lima (1966), Arroyo (2000), Fontana (2005), Nóvoa (1992), Novaes (1992) and (iii) Normal School: Silva (2009; 2001), Carvalho (1998), Olinda (2005), Holanda (2001). Beyond those authors, we searched in documental sources, Brazilian educational legislation and newspapers. About the methodology, the research was classified as qualitative and case study using semitructured interviews and testimonials with sixteen (16) subject of which ten (10) normalistas: two (2) of the 2nd class and eight (8) of the 3rd class; the husband of a “normalista”; the Colonel Pergentino Maia’s grandson; the director of the intermediary public file; the current director and 2 (two) institution employees. The results showed that although the “normalistas” had experienced major challenges during the course, such as the move to a building under renovations, the neighborhood still being structured, and the educational context reformulating guidelines for the Normal School (1958-1959), we conclude that the tradition of graduating in the Normal School cearense, prevailed because it was the primary institution in the education of teachers for the initial courses.